2013
DOI: 10.1111/cxo.12026
|View full text |Cite
|
Sign up to set email alerts
|

Marfan's syndrome: a refractive challenge for optometrists

Abstract: We present an interesting case of a child with Marfan's syndrome with ectopia lentis, who was followed for five years. The changes in refractive and visual findings of this child during this period are discussed. The importance of careful oculo-visual examination and possible management options in such children are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…Other reported ocular manifestations of MFS include cataract, glaucoma, and retinal detachment. 14 , 16 , 17 , 50 Cataract has been reported in mouse models of MFS, 35 yet in this study we have not observed opacifications in the lenses of the fbn1 zebrafish mutants. Although the induced mutation in the fbn1 re12 is predicted to lead to a premature stop codon and thus truncated protein, we cannot rule out that the phenotypic differences observed in the fbn1 re12 , that is, the lack of axial elongation and cataract development, might be explained by a (partially) remaining functionality of the truncated protein product.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Other reported ocular manifestations of MFS include cataract, glaucoma, and retinal detachment. 14 , 16 , 17 , 50 Cataract has been reported in mouse models of MFS, 35 yet in this study we have not observed opacifications in the lenses of the fbn1 zebrafish mutants. Although the induced mutation in the fbn1 re12 is predicted to lead to a premature stop codon and thus truncated protein, we cannot rule out that the phenotypic differences observed in the fbn1 re12 , that is, the lack of axial elongation and cataract development, might be explained by a (partially) remaining functionality of the truncated protein product.…”
Section: Discussioncontrasting
confidence: 50%
“…Increased axial length will result in myopia, flatter corneas will lead to hyperopia, and ectopia lentis can induce myopia, high astigmatism (in cases of partial lens subluxation), or high hyperopia (in cases of complete lens subluxation). 16 , 17 , 50 , 53 In the fbn1 mutant, we found a strong hyperopic shift in the refractive status of the eye, but no changes in the axial length. The hyperopic shift observed in the fbn1 mutant fish is explained by two factors: (1) in zebrafish, the spherical lens is responsible for the full optical power of the eye (the refractive index of the cornea and water is nearly identical, and thus corneal curvature does not contribute to refraction), and (2) the posterior subluxation of the lens caused the optical field to shift backwards.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…With significant lens subluxation, clear view through the lens is impossible and aphakic eyeglasses should be prescribed. [19]…”
Section: Introductionmentioning
confidence: 99%